Distal extrahepatic cholangiocarcinoma mimicking groove pancreatitis: A case report and literature review - Han, Chaoqun; Ling, Xin; Sheng, Liping; Yang, Ming; Lin, Rong; Ding, Zhen (Frontiers in Oncology, 2022)
Abstract Background: The differential diagnosis between cholangiocarcinoma and groove pancreatitis is quite challenging. Groove pancreatitis is commonly misdiagnosed as periampullary tumors. We reported a case of distal extrahepatic cholangiocarcinoma mimicking groove pancreatitis. Case report: A 57-year-old male patient was transferred to our hospital after endoscopic retrograde cholangiopancreatography (ERCP) with stent placement in common bile duct due to obstructive jaundice at local hospital. Groove pancreatitis was considered based on the clinical manifestations and multiple examinations (including computed tomography (CT), magnetic resonance cholangiopancreatography (MRCP) and endoscopic ultrasonography (EUS)). The patient’s symptoms and laboratory investigations almost returned to normal after conservative treatments. Interestingly, the symptoms and laboratory investigations deteriorated after the stent was removed. We performed the second EUS process which found a lesion in lower common bile duct. Finally, he underwent pancreatoduodenectomy and the diagnosis was confirmed as moderately differentiated adenocarcinoma of common bile duct. Conclusion: Our case highlights the fact that distal extrahepatic cholangiocarcinoma which is a malignant disease, can mimic a benign condition like groove pancreatitis. Our case also raises the concern that performing stent placement through ERCP to relieve jaundice without a clear diagnosis could interfere further evaluation of the disease.